Peggotty’s Work-Box: Victorian Souvenirs and Material Memory - Pettitt, Clare (Romanticism and Victorianism on the Net, 2009)
AbstractThis article considers what we can and cannot learn from objects in texts. As its chief example, it takes Peggotty’s workbox in Charles Dickens’s David Copperfield and, through this particular object in a particular text, thinks about how far it is legitimate to “read” cultural-social-historical meanings back into a text, and how far objects in texts operate differently than objects in the world. It then reads the workbox as a marker of memory in the novel, challenging Nicholas Dames’s “associationist” reading of David Copperfield in his Amensiac Selves. The essay ends by considering some of the problems and potentials of “thing theory” in literary studies.